Kepala Sekolah Sebagai Pemimpin Dan Manajer Sekolah - Samsilayurni, Samsilayurni (Journal of Innovation in Teaching and Instructional Media, 2022)
This study aims to determine the duties of a principal as a leader and as a manager to improve the competence of teachers, staff, and all students in the school. As a leader, the principal must be able to provide guidance and supervision, as well as increase the willingness and ability of education staff, open two-way communication and be ready to delegate tasks. As a manager, the principal can deal with various problems at school, thinks analytically, conceptually, always tries to be an intermediary in solving various problems. For this reason, a school principal needs to have the right strategy to establish a harmonious relationship with the environment and have the right strategy to motivate education staff in carrying out various tasks and functions. This study uses a qualitative approach, by describing and outlining the functions and duties of the principal as a leader and manager in the school. Data collection techniques using library research (Library Research) by collecting materials that have to do with research originating from books, scientific journals, literature, and other publications that are worthy of being used as research sources that the author will examine. The results of this study provide comprehensive information and understanding of the principal as a school leader and manager, both in terms of his function and his duties in managing the education unit.